Formation of Student’s Scientific and Cognitive Potential in the Process of Teaching the Course “General Linguistics”: Potential and Competence (Eurasian Journal of Philology Science and Education, 2025)
This article examines the pedagogical potential of the course “General Linguistics” for developing students’ scientific and cognitive potential in higher education. The study aims to clarify the relationship between the concepts of potential and competence and to justify a competence-based framework that fosters scientific thinking, research motivation, and analytical skills in future philologists. The methodology integrates systematization and critical analysis of national and international scholarship in pedagogy, psychology, and linguistics; comparative review of major theoretical approaches; analysis and selection of textbooks and foundational works used in teaching “General Linguistics”; and comparison of traditional and innovative instructional methods designed to enhance students’ research-oriented learning. The findings demonstrate that competence reflects abilities already manifested in practice, whereas potential denotes latent resources and capacities that can be activated under appropriate educational conditions. Consequently, purposeful competence development functions as a mechanism for revealing and expanding students’ scientific and cognitive potential. The article argues for a structured system of competencies subject-specific, interdisciplinary, meta-disciplinary, and research competence and explains how each contributes to core academic outcomes: problem formulation, hypothesis building, data analysis, critical evaluation of linguistic theories, and reflective monitoring of learning results. It is concluded that “General Linguistics,” as a foundational discipline, provides a coherent platform for strengthening functional literacy, cultivating research culture, and preparing students for interdisciplinary challenges in contemporary linguistics and related professional domains.In addition, the paper outlines principles for designing a set of research-oriented learning tasks (problem formulation, data-based work, mini-research projects, academic argumentation, and reflection) and proposes basic criteria for assessing these outcomes within the course. The proposed framework may inform curriculum renewal, the integration of digital/corpus-based data practices, and the planning of students’ individual learning trajectories aligned with research goals.Keywords: General Linguistics, scientific and cognitive potential, competence, research competence, meta-disciplinary skills, philology education.